Master Data Management: A Review - Singh, Saravjeet; Singh, Jaiteg (International Journal of Computer Sciences and Engineering, 2015)
Master data management helps companies to handle and maintain consistent and complete information of master data. Master data orchestration and knowledge extraction are the two biggest problem related to master data. Due to these two predicaments master data management is necessary for effective organization of master data. Master data is type of organizational data but not meta data and use for decision making and business intelligence. Master data in an enterprise is structured data and flows between different component of an enterprise under one’s control. Common master data domains include person (customers, supplier, and controller), products (item), and location and other specific data. As an outcome of MDM, organizations have higher quality product, reliable data, consistent master data records and probable dedicated and interested consumer. This paper presents an overview of master data’s content, scope, sample, advantages, master data management process, tool and techniques and challenges.